„Ich rede jetzt nicht direkt persönlich, denn ich bin darüber momentan hinaus …“ Der Suizid als Selbsttechnik der Subjektspaltung am Beispiel von Horváths Glaube, Liebe, Hoffnung. - Osmanović, Erkan (Brünner Beiträge zur Germanistik und Nordistik)
Luhmann states that the individuality of people varies from one individuality of inclusion to another exclusive individuality. In stratified societies it was measured by which layer or class one belonged. In functionally differentiated societies there is a fragmentation of the subject. To deal with this experience, Elisabeth in Horváths play Glaube, Liebe, Hoffnung, uses her suicide in the service of a subject fission. The term „subject fission“ subsumes various self-techniques that have been used since antiquity and arose in the context of a concern for themselves. To what extent suicide also assumes this function for Elisabeth, is elaborated in the text analysis.